COOPERATIVE TYPE NUMBERED HEADS TOGETHER EFFECT ON STUDENT’S ACHIEVEMENT IN EXPANSION TOPIC - Lucius Marbun .; Motlan . (UNIVERSITAS NEGERI MEDAN, 2015)
ABSTRACT This research was aimed to know 1) Student’s achievement in physics by using numbered heads together (NHT). 2) Student’s achievement in physics by using conventional learning model. 3) The effect of numbered heads together (NHT) on student’s achievement especially on expansion topic. The population was nine classes student grade VII in SMP N 1 Tebing Tinggi. The sample was two classes obtained by cluster random sampling. The sample was VII5 by using numbered heads together (NHT) and VII4 by using conventional learning model. Instrument has 20 questions and tested validated. The mean of pre-test in VII5 was 38.15 and in VII4 was 38.52. After that learning model applied, and then done the post-test. The mean of post-test in VII5 was 78.15 and in VII4 was 73.52. In hypothesis testing obtained tcount > ttable at significant level 0.05. So, can be concluded student’s achievement of VII5 better than VII4. Keywords: Numbered Heads Together, Student’s Achievement